JTS: tools for implementing domain-specific languages - Batory, D.; Lofaso, B.; Smaragdakis, Y. (Proceedings. Fifth International Conference on Software Reuse (Cat. No.98TB100203), 1998)
The Jakarta Tool Suite (JTS) aims to reduce substantially the cost of generator development by providing domain-independent tools for creating domain-specific languages and component-based generators called GenVoca generators. JTS is a set of precompiler-compiler tools for extending industrial programming languages (e.g., Java) with domain-specific constructs. JTS is itself a GenVoca generator where precompilers for JTS-extended languages are constructed from components.